Indonesia's Digital Economic Policy To Increase Economic Resilience - Muhamad Samingan; Lukman Yudho Prakoso; Suwito, Suwito (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The growth of information and communication technology (ICT) has changed the way people live their lives and conduct business. The era of the Industrial Revolution 4.0, characterized by the use of digital technology and the Internet of Things (IoT), has created a new economic environment known as the “digital economy." In this context, digital economy policy becomes very important to support sustainable economic growth and improve national economic resilience. This research aims to analyze Indonesia's digital economy policy in developing the digital economy in the context of Society 5.0 and Industrial Revolution 4.0. The main focus of the research is how government policies can strengthen the national economy. This research uses a descriptive-qualitative method with secondary data collected through a systematic review. Data were collected from various scholarly sources, including relevant journals, research publications, reports, and websites. This qualitative approach generates descriptive notes and data that are integrated into the text for further analysis. When policies are implemented correctly, that is, by paying attention to and realizing the various aspects that have an impact on the policy implementation process, it will produce the maximum benefits, including the Integration, Interactivity, Transparency, Control, and Accountability (IITCA) factors. The research shows that digital economy policies have a significant positive impact on economic growth and resilience. The implementation of the Digital Economic Agreement Framework (DEFA) is expected to strengthen the MSME sector, attract investment, encourage innovation, increase productivity, and create high-quality jobs. The establishment of the Digital Innovation and Sustainable Economy Center (DISC) also plays an important role in supporting the transformation of businesses and organizations towards a sustainable digital economy. In addition, the Indonesian government has improved digital infrastructure, such as 4G networks, 5G technology, and low-earth orbit satellites, and launched digital literacy and skills programs to reduce the digital divide and strengthen economic resilience. An effective digital economy policy can be a powerful instrument to strengthen a country's economic resilience. Research results confirm that the implementation of digital economy policies not only drives economic growth but also improves social and financial inclusion. Collaboration between the public sector, the business world, and civil society is essential for the successful implementation of this policy. In addition, transparency and accountability in the implementation of digital policies, such as through the use of blockchain technology and digital payment systems, can reduce corruption and ensure that government assistance and support are well-targeted. Overall, digital economy policies play an important role in strengthening national economic resilience amid the challenges and opportunities of the digital era.